2021
DOI: 10.1021/acsami.0c20990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Anionic Zinc-Adeninate Metal–Organic Framework Structure on the Luminescent Detection of Rare Earth Ions in Aqueous Streams

Abstract: Rare earth elements (REEs) are critical to numerous technologies; however, a combination of increasing demand, environmental concerns, and monopolistic marketplace conditions has spurred interest in boosting the domestic REE production from sources such as coal utilization byproducts. The economic viability of this approach requires rapid, inexpensive, and sensitive analytical techniques capable of characterizing the REE content during resource exploration and downstream REE processing (e.g., analyzing REE sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…The LODs of the best-performing sensor at low pH, T90W, are below 5 ppb over the pH 3–7 range, even at 1 μM T90W (Table ). Even at pH 3, our LOD values are similar to (or better than) the lowest values reported for other complexes, which are often reported at pH 7. , These results suggested that T90W-LanM might be robust enough to detect Tb III even in challenging environmental samples.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The LODs of the best-performing sensor at low pH, T90W, are below 5 ppb over the pH 3–7 range, even at 1 μM T90W (Table ). Even at pH 3, our LOD values are similar to (or better than) the lowest values reported for other complexes, which are often reported at pH 7. , These results suggested that T90W-LanM might be robust enough to detect Tb III even in challenging environmental samples.…”
Section: Resultssupporting
confidence: 86%
“…However, when this sensor was applied in an AMD sample containing ∼1 ppb Tb III at pH 3.4, the sample had to be spiked with 800 ppb (5 μM) Tb III to be able to observe a signal. 42 By contrast, simply adding T90W-LanM directly to AMD detects and quantifies 3 ppb Tb III present in AMD at pH 3.24 without any spiking. This comparison shows that the high affinity and selectivity of LanM for lanthanides provides a significant advantage over conventional REE sensitizer ligands, which (while they may have high affinity) usually do not have sufficient selectivity to work well in complex solutions like AMD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…84,85 Photofunctionality can be introduced into MOF thin films through a variety of ways: 86 the use of chromophoric organic linkers within the MOF structures, 87 optically-active metal centers (particularly emissive lanthanides), 88 or via host-guest interactions, in which photoactive ions, 89,90 metal complexes, 91,92 molecules, 93-96 nanoparticles, 97-100 and/or other species are encapsulated by the MOF. MOF-based optical sensors are intriguing because they typically exhibit rapid response times (often on the order of seconds), [101][102][103][104] high sensitivity (ppb or lower LOD), 103,105,106 recyclability (via removal of analyte from the MOF after each sensing cycle), 103,104,[107][108][109] and usually can be integrated with inexpensive, portable equipment, 90 such as fiber optic-based platforms. 104,110,111 Indeed, many optical sensors allow for naked-eye detection of analytes and require only simple laser pointers, lightemitting diodes, UV lamps, or other portable excitation sources for operation.…”
Section: Optical Mof Thin Film Sensorsmentioning
confidence: 99%
“…82 For example, Yang and co-workers demonstrated that Cu 2+ selectively undergoes partial ion exchange with terbium in a terbium-succinate MOF, which disrupts the sensitization of terbium and reduces emission (Figure 8H). 129 For "turn off" sensors, insights into the emission quenching mechanism may be gained through a Stern-Volmer analysis of the quenching 106,168 and through timeresolved studies. 169 A key challenge is the development of sensors that exhibit a selective emission response only in the presence of a target ion, hence it is crucial for the sensor to be tested on a multitude of potential interferants that may be encountered in "real-world" systems, such as environmental waters and biological matrices.…”
Section: Examples Of Luminescence-based Mof Thin Film Sensorsmentioning
confidence: 99%